2020
DOI: 10.1007/s10921-020-00719-9
|View full text |Cite
|
Sign up to set email alerts
|

Using Deep Learning for Defect Classification on a Small Weld X-ray Image Dataset

Abstract: This document provides a comparative evaluation of the performance of a deep learning network for different combinations of parameters and hyper-parameters. Although there are numerous studies that report on performance in deep learning networks for ordinary data sets, their performance on small data sets is much less evaluated. The objective of this work is to demonstrate that such a challenging small data set, such as a welding X-ray image data set, can be trained and evaluated obtaining high precision and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…However, the results indicated that the PCA pre-processing led to nonlinear information losses, which had a deleterious influence on the training process. Furthermore, Ajmi et al [36] implemented data augmentation techniques, simultaneously replacing the channel substitution with a Canny edge image and an Adaptive Gaussian thresholding image on the Weld X-ray image dataset. This method seems to provide a great improvement for providing more specific information to the training model.…”
Section: Deep-learning-based Methods For Light Defect Datasetmentioning
confidence: 99%
“…However, the results indicated that the PCA pre-processing led to nonlinear information losses, which had a deleterious influence on the training process. Furthermore, Ajmi et al [36] implemented data augmentation techniques, simultaneously replacing the channel substitution with a Canny edge image and an Adaptive Gaussian thresholding image on the Weld X-ray image dataset. This method seems to provide a great improvement for providing more specific information to the training model.…”
Section: Deep-learning-based Methods For Light Defect Datasetmentioning
confidence: 99%
“…In the process of capturing the target from different angles, the internal parameters of the camera are regarded as constant, and the external parameters are different from each shooting angle. e number of optimized parameters increases significantly with the increase of the target image [7][8][9]. Rodrigues rotation equation provides a method of using vector to represent rotation.…”
Section: Camera Calibrationmentioning
confidence: 99%
“…Shevchik et al (2020) proposed a method that could detect defects in process instability in real time based on a deep Artificial Neural Network (ANN); finally, the quality classification confidence was between 71% and 99%, revealing excellent application values [18]. Ajmi et al (2020) provided a comparative evaluation method of deep learning network performance for different combinations of parameters and hyperparameters and added an enhanced learning method to the dataset, which increased the model accuracy by approximately 3% [19]. Ajmi et al (2020) also applied Machine Learning (ML) and image processing tools to traditional crack detection and proposed a novel classification method based on deep learning networks using data enhancement for random image transformation on the data; it turned out that the model had the best performance in a short time [20].…”
Section: Introductionmentioning
confidence: 99%